2008
DOI: 10.1161/circulationaha.107.729277
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Exercise Electrocardiography Responses and Coronary Heart Disease Mortality Among Men With Diabetes Mellitus

Abstract: Background-An abnormal ECG during maximal exercise testing has been shown to be a powerful predictor of future coronary heart disease (CHD) mortality in asymptomatic men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…We also found that men with higher CRF levels had higher survival rates when compared with unfit men and that abnormal E-ECG test results were associated with an increased risk of all-cause mortality. 4,25,26 Our current results further strengthen the prognostic power of E-ECG testing in men with MetS.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…We also found that men with higher CRF levels had higher survival rates when compared with unfit men and that abnormal E-ECG test results were associated with an increased risk of all-cause mortality. 4,25,26 Our current results further strengthen the prognostic power of E-ECG testing in men with MetS.…”
Section: Discussionsupporting
confidence: 72%
“…Our results suggested that equivocal and abnormal E-ECG responses were associated with higher risk of all-cause, CVD, and CHD mortality. 4 In previous studies, exercise testing has been shown to be an important predictor of survival. 4, 24 Prakash et al 24 found that abnormal E-ECG test results were significantly more common in those who died during the follow-up, and exercise capacity (<5 METs) was independently and significantly associated with all-cause mortality.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations